Longitudinal Changes of Axial Length and Associated Factors in Congenital Ectopia Lentis Patients - Jingxin He; Zhangkai Lian; Qianzhong Cao; Zhenzhen Liu; Charlotte Aimee Young; Xinyu Zhang; Danying Zheng; Guangming Jin (Journal of Ophthalmology)
Purpose. To investigate the longitudinal changes and associated factors of axial length (AL) in congenital ectopia lentis (CEL) patients. Methods. In this retrospective study, medical records of CEL patients were reviewed from January 2014 to December 2019 at the Zhongshan Ophthalmic (ZOC) in China. Patients were divided into the surgery group and the nonsurgery group. Data of refractive power, best-corrected visual acuity (BCVA), and intraocular pressure (IOP) as well as ocular biometrics including AL, corneal curvature, white-to-white (WTW), and central corneal thickness (CCT) were collected at baseline and each follow-up visit. Multiple linear regression was performed to assess the potential associated factors for axial length growth in congenital ectopia lentis patients. Results. Compared with the nonsurgery group, the change rate of AL among children aged 3 to 6 years old was slower in the surgery group (0.443 ± 0.340 mm/year vs. 0.278 ± 0.227 mm/year, P<0.05). However, no statistically significant difference for the change rate of AL was detected between the surgery group and the nonsurgery group (P>0.05) among patients aged 7 years or older. For the surgery group, the results of the linear regression model showed that a higher change rate of AL was associated with younger age (older age: β = −0.009, 95% CI: −0.014 to −0.003, and P=0.002) and worse baseline BCVA (logMAR) (β = 0.256, 95% CI: 0.072 to 0.439, and P=0.007). As for the nonsurgery group, younger baseline age (older age: β = −0.027, 95% CI: −0.048 to −0.007, and P=0.01) and longer baseline AL (β = 0.073, 95% CI: 0.023 to 0.122, and P=0.006) were associated with a higher change rate of AL. Conclusions. The AL change rate was clearly associated with age both in the surgery group and in the nonsurgery group. Intervention strategies such as surgery should be performed earlier for CEL that meets the surgical criteria. Worse baseline BCVA and longer baseline AL are associated factors that would affect the growth rate of AL in the surgery and nonsurgery group, respectively.